Peninjauan Secara Kuantitatif Atas Kinerja Karyawan Berdasarkan Lingkungan Kerja Fisik Dan Disiplin Kerja Pada Pt. Jas Cengkareng Divisi Manifest Cargo Export - Andreas Boris Herlamba Pasaribu; Risza Putri Elburdah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of Physical Work Environment and Work Discipline on employee performance at PT. JAS Cengkareng Manifest Cargo Export Division Jakarta both partially and simultaneously. This study uses a quantitative method through an descriptive approach. The sampling technique in this study uses a non-probability sampling technique, namely a saturated sample with a total of 50 respondents taken from all company employees. Data analysis techniques used are: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, simple & multiple regression test, partial & simultaneous correlation coefficient tg yest, partial & simultaneous determination coefficient test, T test and F test. Based on the results of the multiple linear regression test, the equation Y = 9.186 + 0.314X1 + 0.472X2 is obtained, indicating that the variables of Physical Work Environment and Work Discipline have a positive coefficient on the Employee Performance variable. The coefficient of the Physical Work Environment variable gives a value of 0.314, indicating that if the Physical Work Environment variable increases with the assumption that other variables remain constant, the Employee Performance variable will increase. The coefficient for the Work Discipline variable is 0.472, indicating that an increase in Work Discipline will increase employee performance. The correlation value, or R-value, of 0.772 and the R-square value of 0.596, or 59.6%, indicate a strong relationship between the Physical Work Environment and Work Discipline and employee performance. The F-test also yielded a value of 45.679 > 2.750. This indicates that Ho3 is rejected and Ha3 is accepted. Therefore, it can be concluded that the Physical Work Environment and Work Discipline influence employee performance.